Increased co-expression of TIM-3 with TIGIT or 2B4 on CD8+ T cells is associated with poor prognosis in locally advanced nasopharyngeal carcinoma - Xiaolin Xie; Yaning Feng; Peiwen Fan; Danning Dong; Xuan Yao; Yanchun Peng; Ruozheng Wang (Biomolecules & Biomedicine, 2023)
The use of immune checkpoint inhibitors in malignant tumors improves patient outcomes. Because single-agent immune checkpoint blockade has a low objective response rate, it is meaningful to explore combined blockade of immune checkpoint receptors. We aimed to investigate the co-expression of TIM-3 with TIGIT or 2B4 on peripheral blood CD8+ T cells from patients with locally advanced nasopharyngeal carcinoma. The correlation between co-expression level and clinical characteristics and prognosis was studied to provide a basis for immunotherapy for nasopharyngeal carcinoma. Flow cytometry was used to detect TIM-3/TIGIT and TIM-3/2B4 co-expression on CD8+ T cells. The differences in co-expression between patients and healthy controls were analyzed. The correlation between co-expression of TIM-3/TIGIT or TIM-3/2B4 and the patient clinical characteristics and prognosis was examined. Also, the correlation between the TIM-3/TIGIT or 2B4 co-expression and other common inhibitory receptors was analyzed. We further validated our results using mRNA data from the Gene Expression Omnibus (GEO) database. TIM-3/TIGIT and TIM-3/2B4 co-expression was upregulated on peripheral blood CD8+ T cells from patients with nasopharyngeal carcinoma. They were both correlated with poor prognosis. There was a correlation between TIM-3/TIGIT co-expression and patient age and pathological stage, whereas TIM-3/2B4 co-expression correlated with age and sex. CD8+ T cells with elevated mRNA levels of TIM3/TIGIT and TIM3/2B4 also showed increased expression of multiple inhibitory receptors, indicating T cell exhaustion in locally advanced nasopharyngeal carcinoma. TIM-3/TIGIT or TIM-3/2B4 can be used as potential targets for combination immunotherapy in locally advanced nasopharyngeal carcinoma.